Effects of soluble Klotho and Wnt/β-catenin signaling pathway in vascular calcification in chronic kidney disease model rats and the intervention of Shenyuan granules - Xinrong Zou; Changjiang Wang; Lan Wang; Shenghua Huang; Danfang Deng; Lamei Lin; Xiaoqin Wang (Renal Failure)
Objective This study aimed to investigate the effect of the soluble Klotho (sKlotho)/Wnt/β-catenin signaling pathway on vascular calcification in rat models of chronic kidney disease (CKD) and the intervention effect of Shenyuan granules.Methods Rats with 5/6 nephrectomy and high phosphorus feeding were used to establish the vascular calcification model. The rats were given gradient doses of Shenyuan granules aqueous solution and calcitriol solution by gavage for 8 weeks, which were divided into experimental group and positive control group.Results The 5/6 nephrectomy combined with high phosphorus feeding induced thoracic aortic calcification in rats. Shenyuan granules intervention increased the serum sKlotho level, inhibited the mRNA and protein expression of Wnt1, β-catenin, and Runx2 in the thoracic aorta, and alleviated thoracic aortic media calcification in rats.Conclusion Shenyuan granules may partially regulate the Wnt/β-catenin signaling pathway via serum sKl to interfere with the expression of Runx2, thereby improving vascular calcification in CKD.